2021
DOI: 10.1038/s42003-021-02036-x
|View full text |Cite
|
Sign up to set email alerts
|

Gut mycobiota alterations in patients with COVID-19 and H1N1 infections and their associations with clinical features

Abstract: The relationship between gut microbes and COVID-19 or H1N1 infections is not fully understood. Here, we compared the gut mycobiota of 67 COVID-19 patients, 35 H1N1-infected patients and 48 healthy controls (HCs) using internal transcribed spacer (ITS) 3-ITS4 sequencing and analysed their associations with clinical features and the bacterial microbiota. Compared to HCs, the fungal burden was higher. Fungal mycobiota dysbiosis in both COVID-19 and H1N1-infected patients was mainly characterized by the depletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 52 publications
10
68
0
Order By: Relevance
“…Unstable gut mycobiomes and prolonged dysbiosis persisted in a significant proportion (∼30%) of COVID-19 patients [14] . Another study investigated the gut mycobiota in both COVID-19 and H1N1-infected patients and found increased fungal load and enrichment of fungi, including Candida species, in both groups of patients [68] . Presence of A. niger was positively correlated with diarrhea, while abundance of Penicillium citrinum was inversely correlated with blood levels of CRP [68] .…”
Section: The Gut Mycobiome In Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…Unstable gut mycobiomes and prolonged dysbiosis persisted in a significant proportion (∼30%) of COVID-19 patients [14] . Another study investigated the gut mycobiota in both COVID-19 and H1N1-infected patients and found increased fungal load and enrichment of fungi, including Candida species, in both groups of patients [68] . Presence of A. niger was positively correlated with diarrhea, while abundance of Penicillium citrinum was inversely correlated with blood levels of CRP [68] .…”
Section: The Gut Mycobiome In Covid-19mentioning
confidence: 99%
“…Another study investigated the gut mycobiota in both COVID-19 and H1N1-infected patients and found increased fungal load and enrichment of fungi, including Candida species, in both groups of patients [68] . Presence of A. niger was positively correlated with diarrhea, while abundance of Penicillium citrinum was inversely correlated with blood levels of CRP [68] . Aspergillus infections were recently reported in respiratory tract secretions and tracheal aspirates in patients with COVID-19 [69] , [70] .…”
Section: The Gut Mycobiome In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…2 studies focused on intestinal dysbiosis post COVID-19 infection [ 28 , 33 ] and one study assessed the efficacy of faecal microbiota transplantation post COVID-19 infection [ 34 ]. Eight studies collected the microbiota DNA from stool samples [ 26 31 , 34 , 43 ] while 2 studies collected their samples from rectal swabs [ 32 , 35 ]. Five studies included participants who were administered antimicrobials and/or probiotics prior to sample collection [ 27 , 28 , 30 , 32 , 35 ], 3 studies excluded these participants [ 26 , 31 , 32 ] while 2 studies did not report this information [ 29 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reaction conditions comprised 30 s at 95°C, followed by 40 cycles of 5 s at 95°C and 34 s at 56°C, followed by 15 s at 95°C, 1 min at 60°C and 15 s at 95°C. qPCR calibration curves were constructed using linearized plasmid standards harbouring inserts of the PCR-amplified 16S rRNA gene of Escherichia coli ATCC 25922 as previously described ( 19 , 20 ). Sample DNA was analysed in duplicate.…”
Section: Methodsmentioning
confidence: 99%